Perennial Staple Crops: Yields, Distribution, and Nutrition in the Global Food System - Kreitzman, Maayan; Toensmeier, Eric; Chan, Kai M. A.; Smukler, Sean; Ramankutty, Navin (Frontiers in Sustainable Food Systems, 2020)
Staple crops, which have large amounts of carbohydrates, proteins, and/or fats, provide the bulk of calories in people’s diets. Perennial plants, which can be productive for many years without the need for replanting, can produce staple foods and environmental benefits, but their agronomic and nutritional properties haven’t been considered synthetically in comparison to annual staples. Here we offer a framework to classify perennial staple crops according to their nutritional categories and cultivation status. We assemble literature to report on the yield potential of 51 perennial staple crops, only 15 of which are well characterized in existing global datasets. We show the extent and distribution of perennial staple crop production in relation to annual crop types, calculate the carbon stocks they hold, and analyse their nutritional content for three macronutrients and nine micronutrients. We found that most perennial staple crops are regional crops (not globally traded) that grow in the subtropics to tropics. At least one perennial staple crop in each of the five nutritional categories has yields over 2.5 t/ha, in some cases considerably higher, competitive with and in many cases exceeding those of nutritionally comparable annual staples. Perennial staple crops only comprise ~4.5% of total cropland. They hold a modest ~ 11.4 GtC above and below ground, less than one third of the anthropogenic carbon-equivalent emissions for the year 2018, but more than the ~9 GtC held by the same amount of annual cropland. If linear growth in land under perennial staple production continues to 2040, and replaces only annual cropland, an additional ~ 0.95 GtC could be sequestered. Many perennial crops also had competitive macronutrient density and yield (per unit area) compared to annual staples; moreover, specific perennial staples are abundant in specific micronutrients, indicating that they can be a nutrient-dense part of diets, unlike the most ubiquitous annual staple crops (corn, wheat, rice) that do not appear in the top 85th percentile for any of the nine micronutrients analysed. Transition of land and diets to perennial staple crops, if judiciously managed, can provide win-win solutions for both food production and ecosystems.